Anti-diabetic Effect of Punica granatum Flower Polyphenols Extract in Type 2 Diabetic Rats: Activation of Akt/GSK-3β and Inhibition of IRE1α-XBP1 Pathways - Tang, Dan; Liu, Liu; Ajiakber, Dildar; Ye, Jianping; Xu, Jianjun; Xin, Xuelei; Aisa, Haji Akber (Frontiers in Endocrinology, 2018)
Type 2 diabetes mellitus (T2DM) is the most common type of diabetes with more than hundreds of millions of patients worldwide. However, the medicines for treatment of T2DM are very limited. In China, Punica granatum L. flower (PGF) has been used as an anti-diabetic herb in the herbal medicine. The activity involves in improvement of insulin sensitivity. However, the underlying mechanism of action is elusive. The current study was designed to address this issue by investigating the effect of polyphenols extract of PGF in diabetic rats. A rat model was orally administrated with PGF polyphenols extract at doses of 50 and 100 mg/kg for 4-weeks. Insulin sensitivity was improved as indicated by oral glucose tolerance test (OGTT), insulin tolerance test (ITT) and homeostasis model assessment of insulin resistance (HOMA-IR). At the molecular level, insulin signaling activity was improved with an elevation in insulin-stimulated phosphorylation of insulin receptor substrate (IRS-1), Akt and GSK-3β. Endoplasmic reticulum (ER) stress signals including phosphorylation of inositol-requiring kinase1 (IRE1) and activation of X box binding protein (XBP-1) splicing were decreased by the PGF treatment. Expressions of IRE1α, XBPs and CHOP were all decreased by PGF. Blood lipid profile, liver glycogen content and antioxidant status were improved by PGF in the rats. The observations suggest that PGF is able to lower glucose levels in T2DM rats by improving the insulin resistance. The mechanism is likely related to the activiation of Akt-GSK3β signaling pathway and inhibition of ER stress.